DIFFERENT EXPERIMENTAL MODELS USED TO INDUCE DIABETES MELLITUS IN RODENTS: A REVIEW - CHAKRABORTY, RESHMI; AHMED, ABDUL BAQUEE; SAHA, DIPANKAR (International Journal of Current Pharmaceutical Research, 2019)
Diabetes is a metabolic disease characterized by the presence of hyperglycemia resulting from either defects in insulin secretion or action or both. Various processes are involved in the development of diabetes. These range from autoimmune destruction of the insulin-producing cells, β-cells of the pancreas, a dysfunction of the pancreatic β-cell, and impaired insulin action through insulin resistance. Experimental diabetes in animals are widely induced by administration of alloxan and streptozotocin at a proper dose. The mechanism of their action in pancreatic β-cells has been extensively investigated. Reactive oxygen species are responsible for the cytotoxic action of both these diabetogenic agents. However, the source of their generation is different in the case of alloxan (ALX) and streptozotocin (STZ). In one of the study, it is also showed that the administration of a high-fat diet (HFD) to rats for 16 w showed a progressive increase in body weight, energy intake, abdominal fat deposition, and abdominal circumference along with impaired glucose tolerance, dyslipidemia and hyperinsulinemia. Administration of alloxan or streptozotocin in addition with HFD is also able to induce diabetes in an experimental rat model.